USULAN KEBIJAKAN PELAYANAN LIFT-ON DAN LIFT-OFF PETI KEMAS DI DEPO PETI KEMAS PT X UNTUK MEMINIMASI WAKTU TUNGGU TRUK MENGGUNAKAN SIMULASI KEJADIAN DISKRIT DAN ALGORITMA DISPATCHING - Kalula, Argianti
Total throughput of goods unloaded and loaded at Tanjung Priok Port experienced an increase in the last quarter of 2023. As a result, the quality of logistics services needs to be improved, particularly at Container Depot PT X, located near Tanjung Priok Port in the PT Kawasan Berikat Cakung area. PT X Container Depot is one of the container depots providing lift-on and lift-off services for empty containers, specifically for the retrieval and storage of empty containers. PT X Container Depot has seen an increase in throughput for lift-on and lift-off activities. However, the depot has experienced a decline in service quality, as evidenced by an increase in truck round time, which exceeds the established standards. Therefore, this study aims to address the prolonged truck round time by minimizing the average truck waiting time. The study begins by developing a discrete-event simulation model for the lift-on and lift-off services provided by side loaders under the existing condition of first-come, first-serve, as well as proposed policies such as nearest job first and dispatching with a planning window based on the number of trucks (3 and 6 trucks) and a fixed truck arrival interval of 15 minutes. The nearest job first policy employs a greedy algorithm on a complete graph to determine the service sequence based on the nearest truck position. The dispatching policy uses a dispatching algorithm to minimize the total truck waiting time within the planning window. This policy requires real-time data on truck arrivals. ANOVA and Tukey statistical tests were conducted to determine the proposed policy that results in the lowest average truck waiting time. The selected policy is the dispatching policy with a fixed-time planning window of 15 minutes. Implementing this policy successfully reduced the average truck waiting time by 38.18%, equivalent to a savings of 36.97 seconds, and reduced the total traveling time of the side loader by 6.247%. The study concludes with a recommendation to install an Advanced Traffic Information System (ATIS) to obtain real-time truck arrival data to implement the dispatching policy effectively